Onosma demirizii (Boraginaceae), a new species from central Anatolia, Turkey - Tarimcilar, Gül; Yilmaz, Özer; Kaynak, Gönül (Bangladesh Journal of Botany, 2018)
Onosma demirizii Kaynak, Tarımcılar & Yılmaz sp. nova (Boraginaceae) is described as a new species from central Anatolia, Turkey. This new species is closely related to O. subulifolium H. Riedl but differs by its yellowish-green stems, patent-setose indumentum, linear to narrowly oblanceolate cauline leaves, shorther calyx and corolla and anthers that are longer than the filaments. The diagnostic morphological characters of this new species are discussed.